The impact of artificial intelligence platforms on the e-learning environment in teaching the Arabic language to primary school students - Al-Tlouhi, Raad Jamal (Journal of Curriculum and Teaching Methodology, 2023)
The study aimed to know the impact of artificial intelligence platforms on the e-learning environment in teaching the Arabic language to primary school students. The study used the semi-experimental approach and the analytical descriptive approach. Two groups: one is an experimental group that used artificial intelligence technology in the e-learning environment and consisted of 15 students, and the other represented the control group that used the usual method and consisted of 15 students. Academic achievement in the Arabic language subject The study found that the use of artificial intelligence platforms technology in the e-learning environment has a positive impact on the teaching of the Arabic language subject, and the study recommended the need to employ artificial intelligence techniques to serve the educational and learning process, in order to facilitate the learning process for students.
Keywords: artificial intelligence; artificial intelligence platforms; e-learning; e-learning environment